Comparison of sludge drying performance between microwave and convective drying - Taib, Mohamad Rozainee; W. Ali, W. Khairuddin; Tan, K. G.; Tan, C. H.; Kumoro, A. C. (Faculty of Chemical and Natural Resources Engineering, UTM, 2001)
Drying of the sludge which reduces its volume and mass is an important aspect for sludge management. Experiments were carried out to compare the efficiency between microwave and convective drying. The results showed that microwave drying is more efficient than convective drying up to about 30 times. This is mainly caused by the different drying mechanisms. Microwave penetrate into total mass of sludge and cause water molecules to vibrate rapidly. Vibration of water molecules creates frictional heat and sludge heated volumetrically that avoids limitation of the poor heat conductivity of the material. It was clearly indicated by the core temperature profiles during drying. In microwave drying, the core temperature achieved 85C in less than one minute, while convective drying took about 500 minutes to achieve the same temperature. Higher power level of microwave gave higher drying rate. Hence the energy and time required for the drying process were reduced significantly.